A focussed analysis of β-cyclodextrins for quinoxaline derivatives synthesis - Khatoon, Hena; Abdul Malek, Emilia (Bentham Science Publishers, 2024)
Cyclodextrins (CDs), which are a type of cyclic oligosaccharides, are widely used in supramolecular chemistry. For example, they can be used to encapsulate volatile compounds, such as drugs, within their hydrophobic cavity. This encapsulation reduces the volatility of the compounds and helps to retain their desired properties. Due to its extraordinary properties, cyclodextrins have been utilized as catalysts in numerous organic synthesis processes. An intrinsic objective of organic chemists is to optimize the efficacy of organic synthesis through the mitigation of chemical waste and energy expenditure. Utilizing water as a green solvent is, therefore, economical, environmentally sustainable, and secure. It appears that employing water in conjunction with a recyclable catalyst is the most effective method for supramolecular catalysis. As a consequence, we focused this review on the use of water as a solvent and cyclodextrin as a polymer catalyst to produce quinoxaline derivatives in an environmentally friendly and sustainable manner.